2009
DOI: 10.1007/s00248-008-9482-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacterial Communities Associated with Organic Aggregates in a Large, Shallow, Eutrophic Freshwater Lake (Lake Taihu, China)

Abstract: Although organic-aggregate-associated bacteria play a pivotal role in microbial food webs and in the cycling of major elements, their community composition and diversity have not been extensively studied, especially in shallow freshwater systems. This study is among the first to explore intra-lake horizontal heterogeneity of organic-aggregate-associated bacterial community composition (OABC) in the large, shallow, and eutrophic Lake Taihu. During November 2006, samples were collected at four locations represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
70
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 54 publications
14
70
2
Order By: Relevance
“…The elevated phylogenetic diversity may be attributed to the downward metabolite fluxes that favor niche diversity through the maintenance of various nutrient sources. Furthermore, visual and microscopy observations showed increased levels of suspended particulate and floc matter in the lakes' monimolimnia that may contribute to increased phylogenetic divergence through habitat diversification (Tang et al, 2009). Another hypothesis may be that low oxygen environments have the capacity to maintain a higher variety of energetic pathways than oxygen-rich environments, leading to retention of higher ecological diversity coupled with lowered interspecific competition (Humayoun et al, 2003).…”
Section: Prokaryotic Diversitymentioning
confidence: 99%
“…The elevated phylogenetic diversity may be attributed to the downward metabolite fluxes that favor niche diversity through the maintenance of various nutrient sources. Furthermore, visual and microscopy observations showed increased levels of suspended particulate and floc matter in the lakes' monimolimnia that may contribute to increased phylogenetic divergence through habitat diversification (Tang et al, 2009). Another hypothesis may be that low oxygen environments have the capacity to maintain a higher variety of energetic pathways than oxygen-rich environments, leading to retention of higher ecological diversity coupled with lowered interspecific competition (Humayoun et al, 2003).…”
Section: Prokaryotic Diversitymentioning
confidence: 99%
“…Previous findings have highlighted the importance of Bacteroidetes, formerly known as the Cytophaga-Flavobacteria-Bacteroidetes phylum, on submerged surfaces, suspended particles, and during phytoplankton blooms (Eiler and Bertilsson 2004). Bacteroidetes has been shown especially abundant in samples derived from Cyanobacterial aggregates (Tang et al 2009). In this study, the higher percentage of Bacteroidetes and the only observation of Cyanobacterial in B2 and D7 stations might be reasonable.…”
Section: Bacterial Communities In Comparable Habitsmentioning
confidence: 99%
“…The abundance of attached bacteria was determined by epifluorescence microscopy after DAPI (4 ' ,6-diamidino-2-phenylindole) staining (Porter and Feig, 1980) as described previously (Tang et al, 2009). Total nucleic acids from the particle-attached bacteria on the filters were extracted and purified using proteinase K, sodium dodecyl sulfate concomitant with chloroform extraction and isopropanol precipitation.…”
Section: Total Bacterial Abundance Dna Extraction and Pcr-dggementioning
confidence: 99%
“…Previous study has shown that the abundance of a Bacteroidetes species capable of lysing cyanobacteria cells was tightly coupled to the development of a bloom event (Rashidan and Bird, 2001). Futhermore, Tang et al (2009) also pointed out that members of the Bacteroidetes formed a substantial component of the bacterial communities associated with algae-based organic aggregates in Lake Taihu. Second, Eiler et al (2006) and Maruyama et al (2003) suggested that both Alphaproteobacteria and Betaproteobacteria were dominant in the mucilage of Cyanobacteria during bloom events, and several members of the Proteobacteria can attach to Cyanobacteria and cause cell lyses and death of some cyanobacterial species (Eiler et al, 2006;Maruyama et al, 2003).…”
Section: Phylogenetic Analysis Of the Particle-attached Bacterial Commentioning
confidence: 99%
See 1 more Smart Citation